(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Cermet is a category of materials that combines elements of ceramic and metals to create materials with the greatest qualities of both, including high hardness, resistance to abrasion and wear, resistance to erosion and corrosion, and resistance to deformation under high temperatures. In recent decades, WC-based cermet powders have been coated on steel using a variety of thermal spray processes, including detonation guns, high velocity oxygen or air fuel, plasma spraying,and other cladding methods like tungsten inert gas arc and laser cladding. In recent years, WC-based Cermet coatings on steel have been more well-liked as a possible method for enhancing metallurgical, mechanical, erosion, corrosion and wear qualities. This review paper summarizes the tungsten carbide-based cermet coatings on various grades of steel substrates.